2023
DOI: 10.3847/2041-8213/acaf85
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS–JWST First Results: Mid-infrared Emission Traces Both Gas Column Density and Heating at 100 pc Scales

Abstract: We compare mid-infrared (mid-IR), extinction-corrected Hα, and CO (2–1) emission at 70–160 pc resolution in the first four PHANGS–JWST targets. We report correlation strengths, intensity ratios, and power-law fits relating emission in JWST’s F770W, F1000W, F1130W, and F2100W bands to CO and Hα. At these scales, CO and Hα each correlate strongly with mid-IR emission, and these correlations are each stronger than the one relating CO to Hα emission. This reflects that mid-IR emission simultaneously acts as a dust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 160 publications
6
35
0
Order By: Relevance
“…The F2100W flux fractions are always significantly less than all three shorter-wavelength MIRI bands. Given the present residual ± 0.1 MJy sr −1 uncertainty in the background level of our MIRI images (see Section 2.1 and Leroy et al 2023, this Issue), we assess the impact this has on filament flux fractions by offsetting the image intensities by the uncertainty in a positive and negative sense. Dashes overplotted on the bars of Figure 7 indicate the resulting perturbed fractions.…”
Section: Fraction Of Flux In the Mir Filament Networkmentioning
confidence: 99%
“…The F2100W flux fractions are always significantly less than all three shorter-wavelength MIRI bands. Given the present residual ± 0.1 MJy sr −1 uncertainty in the background level of our MIRI images (see Section 2.1 and Leroy et al 2023, this Issue), we assess the impact this has on filament flux fractions by offsetting the image intensities by the uncertainty in a positive and negative sense. Dashes overplotted on the bars of Figure 7 indicate the resulting perturbed fractions.…”
Section: Fraction Of Flux In the Mir Filament Networkmentioning
confidence: 99%
“…This letter demonstrates the potential for new PHANGS-JWST observations to be used to identify (morphologically) stellar-feedback-powered bubbles, and highlights the need for 14). In color scale is the total column density, which we expect (away from regions of active star formation) to correspond well to the 7.7 μm emission (Leroy et al 2023;Sandstrom et al 2023). The bottom panel shows the isolated galaxy simulation tuned for NGC 628 from E. Emsellem et al (2022, in prepararion).…”
Section: Discussionmentioning
confidence: 85%
“…The middle panel shows the isolated galaxy simulation from Tress et al (2020; the same simulation shown in the bottom panels of their Figure14). In color scale is the total column density, which we expect (away from regions of active star formation) to correspond well to the 7.7 μm emission(Leroy et al 2023;Sandstrom et al 2023). The bottom panel shows the isolated galaxy simulation tuned for NGC 628 from E.Emsellem et al (2022, in prepararion).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The understanding of the MIR of starburst nuclei, and starbursting galaxies in general, will be revolutionized with the recent arrival of JWST. The medium resolution spectrometer (MRS) on the JWST Mid-Infrared Instrument (MIRI) is already allowing for studies of the detailed properties of these objects at spatial scales 7 times smaller, 50 times more sensitive, and with spectral resolutions 5 times higher than those provided by the IRS on Spitzer (Rieke et al 2015;Labiano et al 2021;Leroy et al 2023;Sandstrom et al 2023;Thilker et al 2023).…”
Section: Introductionmentioning
confidence: 99%